Metal oxide nanostructures for sensor applications - Nunes, D. (2019)
Electrorheological fluids have been paying a lot of attention due to their potential use in active control of various devices in mechanics, biomedicine or robotics. An electrorheological fluid consisting of polarizable particles dispersed in a non-conducting liquid is considered to be one of the most interesting and important smart fluids. This work presents the effect of the dopant, camphorsulphonic acid or citric acid, on the electrorheological behaviour of suspensions of doped polyaniline nanostructures dispersed in silicone oil, revealing its key role. The influence of carbon nanoparticle concentration has also been studied for these dispersions. All the samples showed an electrorheological effect, which increased with electric field and nanostructure concentration and decreased with silicone oil viscosity. However, the magnitude of this effect was strongly influenced not only by carbon nanoparticle concentration but also by the dopant material. The electrorheological effect was much lower with a higher carbon nanoparticle concentration and doped with citric acid. The latter is probably due to the different acidities of the dopants that lead to a different conductivity of polyaniline nanostructures. Furthermore, the effect of the carbon nanoparticles could be related to its charge trapping mechanism, while the charge transfer through the polymeric backbone occurs by hopping. Polyaniline/camphorsulphonic acid composite nanostructures dispersed in silicone oil exhibited the highest electrorheological activity, higher than three decades increase in apparent viscosity for low shear rates and high electric fields, showing their potential application as electrorheological smart materials.